An easy way to detect dengue virus using nanoparticle-antibody conjugates - Basso, Caroline R. [UNESP]; Tozato, Claudia C. [UNESP]; Crulhas, Bruno P. [UNESP]; Castro, Gustavo R. [UNESP]; Junior, João Pessoa A. [UNESP]; Pedrosa, Valber A. [UNESP] (Elsevier, 2018)
The aim of the present research is to propose a new method based on localized surface plasmon resonance (LSPR) for fast dengue virus detection. A pool with four dengue serotypes (DENV-1, -2, -3, -4) was detected through antigen-antibody binding using gold nanoparticles (AuNPs) as signaling antibody carriers. Such result was confirmed through surface plasmon resonance (SPR), transmission electron microcopy (TEM), and dynamic light scattering (DLS) techniques. The limit of detection was calculated for TCID50 107 demonstrating a linear correlation between viral concentration and number of cells with an r2 value of > 0.993. The assay presented good sensibility and reproducibility of results and the negative controls were not mistakenly detected. This design requires no pretreatment or high trained person. In the future, it can be used in commercial antibody detection kits.
Keywords: Biosensor; Fast detection; Infectious diagnostics